Democracy in decline? - Diamond, Larry Jay.; Plattner, Marc F., 1945- (Baltimore, Maryland, John Hopkins University Press, 2015)
"For almost a decade, Freedom House's annual survey has highlighted a decline in democracy in most regions of the globe. While some analysts draw upon this evidence to argue that the world has entered a "democratic recession," others dispute that interpretation, emphasizing instead democracy's success in maintaining the huge gains it made during the last quarter of the twentieth century. Discussion of this question has moved beyond disputes about how many countries should be classified as democratic to embrace a host of wider concerns about the health of democracy: the poor economic and political performance of advanced democracies, the new self-confidence and assertiveness of a number of leading authoritarian countries, and a geopolitical weakening of democracies relative to these resurgent authoritarians. In Democracy in Decline?, eight of the world's leading public intellectuals and scholars of democracy--Francis Fukuyama, Robert Kagan, Philippe C. Schmitter, Steven Levitsky, Lucan Way, Thomas Carothers, and editors Larry Diamond and Marc F. Plattner--explore these concerns and offer competing viewpoints about the state of democracy today. This short collection of essays is essential reading for anyone wanting to understand the latest thinking on one of the most critical questions of our era"--Provided by publisher.
"Is Democracy in Decline? is a short book that takes up the fascinating question on whether this once-revolutionary form of government--the bedrock of Western liberalism--is fast disappearing. Has the growth of corporate capitalism, mass economic inequality, and endemic corruption reversed the spread of democracy worldwide? In this incisive collection, leading thinkers address this disturbing and critically important issue. Published as part of the National Endowment for Democracy's 25th anniversary--and drawn from articles forthcoming in the Journal of Democracy--this collection includes seven essays from a stellar group of democracy scholars: Francis Fukuyama, Robert Kagan, Thomas Carothers, Marc Plattner, Larry Diamond, Philippe Schmitter, Steven Levitsky, Ivan Krastev, and Lucan Way. Written in a thought-provoking style from seven different perspectives, this book provides an eye-opening look at how the very foundation of Western political culture may be imperiled"--Provided by publisher.
Introduction / Marc Plattner -- Why is Democracy Performing so Poorly? / Francis Fukuyama -- The Weight of Geopolitics / Robert Kagan -- Crisis and Transition, but not Decline / Philippe C. Schmitter -- The Myth of Democratic Recession / Steven Levitsky & Lucan Way -- Democracy Aid at 25 : Time to Choose / Thomas Carothers -- Conclusion : Facing Up to the Democratic Recession / Larry Diamond.
Includes bibliographical references and index.
Keywords: 2000-2099; Democracy; Democratization; World politics -- 21st century; Democracy; Democratization; World politics